The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/chem.201805493
|View full text |Cite
|
Sign up to set email alerts
|

Transition‐Metal Acetate‐Promoted Intramolecular Nitrene Insertion to Vinylogous Carbonates for Divergent Synthesis of Azirinobenzoxazoles and Benzoxazines

Abstract: Synthesis and isolation of highly unstable azirinobenzoxazole and benzoxazines in a chemodivergent fashion from aryl azido vinylogous carbonates by simple change in transition metal acetate is described. Thermal or rhodium(II) acetate‐mediated decomposition of these azides gave dihydroazirino benzoxazole. Their nickel(II) acetate‐promoted reaction gave 4‐dihydro‐2H‐benzoxazines, whereas copper(II) acetate led to the corresponding oxidized imine derivatives. Benzaoxazine derivative could be kinetically resolved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Nitrenes (R–N) are highly reactive intermediates that have been fascinating chemists for decades. As versatile reagents, nitrenes can be easily generated through either thermal, photolytic, or catalytic decomposition of their corresponding azide precursors (R–N 3 ). They have been broadly used in diverse chemical transformations such as C–H amination , and intramolecular insertion for the synthesis of biologically active N -heterocycles such as azirinobenzoxazole and benzoxazines, and transition-metal-catalyzed synthesis of nitrogen-containing compounds. Transient nitrenes have also been used in functionalization of carbon nanomaterials , and cross-coupling of polymers …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nitrenes (R–N) are highly reactive intermediates that have been fascinating chemists for decades. As versatile reagents, nitrenes can be easily generated through either thermal, photolytic, or catalytic decomposition of their corresponding azide precursors (R–N 3 ). They have been broadly used in diverse chemical transformations such as C–H amination , and intramolecular insertion for the synthesis of biologically active N -heterocycles such as azirinobenzoxazole and benzoxazines, and transition-metal-catalyzed synthesis of nitrogen-containing compounds. Transient nitrenes have also been used in functionalization of carbon nanomaterials , and cross-coupling of polymers …”
Section: Introductionmentioning
confidence: 99%
“…58,59 Photodecomposition of Isonicotinoyl Azide (5). Laser photolysis (266 nm) of isonicotinyl azide (5, Figure 4a) in the N 2 matrix gave rise to a series of new peaks including several signals around 2260 cm −1 (Figure 4b) that are characteristic for the asymmetric NCO stretching vibration to the rearrangement product 4-pyridyl isocyanate (7). The band position is very close to that aforementioned for 3-pyridyl isocyanate (3, 2264.7 cm −1 , N 2 matrix) and previously reported for 2-pyridyl isocyanate (2245 cm −1 , Ar matrix).…”
Section: ■ Introductionmentioning
confidence: 99%
“…7 In this context, decades before azides gained their current popularity as nitrogen sources for the addition of the corresponding nitrenes to alkenes, 8 pioneer work by Huisgen showed that electron-deficient alkenes deliver 1,4-disubstituted triazolines regioselectively when reacted with azides, 9 which might deliver the corresponding aziridines upon nitrogen extrusion (Scheme 2). 10 Subsequent reports of thermolysis 11 or photolysis 12 of triazolines to access aziridines have since emerged in the literature, however, these remain anecdotical in comparison to other methodologies due to selectivity issues. While the presence of electron-withdrawing substituents in triazoline 3 facilitates the cycloaddition step, it also increases the stability of its open-ring isomer that might evolve into aziridine 4 , or a diazo compound 5 .…”
mentioning
confidence: 99%
“…While the presence of electron-withdrawing substituents in triazoline 3 facilitates the cycloaddition step, it also increases the stability of its open-ring isomer that might evolve into aziridine 4 , or a diazo compound 5 . The latter can further react with an alkene to form after tautomerisation 2-pyrazoline 6 , 10,11 or undergo elimination to form an aminoalkane 7 . 13 The fate of these transient 1,4-disubstituted triazolines is strongly dependent on the substituents on either starting material and substantial decomposition is also often observed.…”
mentioning
confidence: 99%